2021
DOI: 10.3390/cancers13102320
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumor Resection in Elderly Patients: Potential Factors of Postoperative Worsening in a Predictive Outcome Model

Abstract: The decision of whether to operate on elderly patients with brain tumors is complex, and influenced by pathology-related and patient-specific factors. This retrospective cohort study, based on a prospectively collected surgical database, aims at identifying possible factors predicting clinical worsening after elective neuro-oncological surgery in elderly patients. Therefore, all patients ≥65 years old who underwent BT resection at a tertiary referral center between 01/2018 and 12/2019 were included. Age, smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In contrast, many other studies have found no association between elderly age and increased risk for complications or mortality following CTR suggesting that CTR is a safe procedure for geriatric patients. For elderly patients who do experience complications, ICH, seizure, DVT, PE, infection, and stroke are most common [ 1 7 8 10 11 12 13 14 15 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, many other studies have found no association between elderly age and increased risk for complications or mortality following CTR suggesting that CTR is a safe procedure for geriatric patients. For elderly patients who do experience complications, ICH, seizure, DVT, PE, infection, and stroke are most common [ 1 7 8 10 11 12 13 14 15 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steinberger et al revealed in their study that old age was an independent predictor of morbidity and mortality in patients undergoing craniotomy for resection of meningioma (9). Ferroli et al reported in their retrospective cohort study that postoperative complications and surgical complexity could significantly influence the early outcome in elderly patients undergoing brain tumor surgery, and postoperative complications was the only factor with a strong correlation to postoperative worsening at the 3-month follow-up (19). In another study, the authors reported that no significant difference was discovered regarding the 30-day mortality rate for elderly versus nonelderly patients, whereas elderly patients had a significantly higher complication rate compared with non-elderly patients (10).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Ferroli P et al investigated different factors for postoperative outcome after brain tumor resection in elderly patients and identified the occurrence of postoperative complications as important factor for postoperative worsening at the 3-month follow-up [ 32 ]. Similarly, we also found that only one of the 11 patients with a symptomatic postsurgical hemorrhage showed improvement of neurological deficits at the 3-month follow-up visit.…”
Section: Discussionmentioning
confidence: 99%